2018
DOI: 10.3343/alm.2018.38.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Macrophage Migration Inhibitory Factor as a Biomarker of Active Pulmonary Tuberculosis

Abstract: BackgroundMacrophage migration inhibitory factor (MIF), a pro-inflammatory cytokine with chemokine-like functions, has been shown to play a central role in several acute and chronic inflammatory diseases. However, limited information is available regarding the use of MIF as an inflammatory pathway marker in patients with tuberculosis. This study aimed to investigate the association of MIF with IFN-γ and TNF-α in active pulmonary tuberculosis (APTB) following anti-tuberculosis treatment.MethodsThe MIF, TNF-α, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
4
0
2
Order By: Relevance
“…In this study, we found that MIF level was significantly decreased ( P < 0.01) in 0, 3 and 6 months after treatment, then it entered into a plateau in 9 to 12 months. Similarly, another study reported decreased MIF levels in 2, 4, and 6 months after treatment ( P < 0.01) [14]. Kuai et al [15] found that TB could be distinguished from other inflammatory phenotype with profiles of serum MIF, IFN-γ and TNF-α, which might make effects in pathogenesis and be available as indicators of active tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, we found that MIF level was significantly decreased ( P < 0.01) in 0, 3 and 6 months after treatment, then it entered into a plateau in 9 to 12 months. Similarly, another study reported decreased MIF levels in 2, 4, and 6 months after treatment ( P < 0.01) [14]. Kuai et al [15] found that TB could be distinguished from other inflammatory phenotype with profiles of serum MIF, IFN-γ and TNF-α, which might make effects in pathogenesis and be available as indicators of active tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
“…MTB infection was hard to be inhibited since the proinflammatory response could be generally suppressed with the excessive generation of anti-inflammatory cytokines [23]. MIF was a critical cytokine responsible for the innate immunity and inflammatory responses, which was reported to make critical effects in both PTB development [24] and severity [14]. Until now, our study has been the first report to measure serum levels of MIF in PTB and further assess its association with the 12-month prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em contrapartida houve um achado particular, citando que há divergência nos resultados dos marcadores e deles para com a sua comparabilidade. Shang et al (2018) investigaram o papel da citocina Fator de Inibição da migração de Macrófagos (MIF) associada ao Fator de Necrose Tumoral α (TNF-α) e IFN-γ no curso da quimioterapia em pacientes chineses hospitalizados. Já no período de pré-tratamento os 47 participantes foram dicotomizados em níveis altos (39) e baixos (8) de MIF, com níveis altos desta sendo relacionados ao TNF-α.…”
Section: Biomarcadores Para Monitoramento Da Terapia E Curaunclassified
“…A respeito das doenças de base listadas nos pacientes do estudo, haviam indivíduos com câncer, diabetes, hepatites B e C e fumantes com história pregressa. Os autores não refletem as repercussões desses quadros na dinâmica dos biomarcadores pesquisados, o que dificulta maiores conclusões (SHANG et al, 2018).…”
Section: Biomarcadores Para Monitoramento Da Terapia E Curaunclassified